Diastereoselective access to [4, 4]-carbospirocycles: governance of thermodynamic enolates with an organocatalyst in vinylogous cascade annulation. Issue 13 (24th January 2022) - Bhajammanavar, Vinod; Mallik, Sumitava; Choutipalli, Venkata Surya Kumar; Subramanian, Venkatesan; Baidya, Mahiuddin
Abstract : A vinylogy concept driven highly diastereoselective cascade protocol towards [4, 4]-carbospirocycles is developed by leveraging a spiro-annulation reaction through the thermodynamic enolate under organocatalysis. Abstract : A vinylogy concept driven annulation strategy is developed to access [4, 4]-carbospirocycles from alkylidene malononitriles and cyclopentene-1, 3-diones. The reaction is catalyzed by an inexpensive organocatalyst and products with three stereocenters were obtained as a single diastereomer in high yields. The spiro-selectivity originates from the reaction of the thermodynamic enolate intermediate which is fundamentally intriguing.